Clinical validation and evaluation of the EasyNAT Malaria assay and the Alethia Malaria assay in a non-endemic setting: rapid and sensitive assays for detecting Plasmodium spp. in returning travellers - Charlotte van der Veer; Julian Apako; Anja Sonneveld-Hendriks; Annemarie Kaak; Cindy Arias-Claro Handgraaf; Erik Schaftenaar; Guido J.H. Bastiaens; Jacky Flipse (Travel Medicine and Infectious Disease)
This study assessed the analytical and clinical performance of the EasyNAT Malaria cross-priming amplification assay and the Alethia Malaria loop-mediated isothermal amplification assay in screening for Plasmodium spp. in febrile patients with recent travel history to malaria endemic regions.Using the composite microbial reference, the overall sensitivity and specificity were: 100 % and 97.5 % for the EasyNAT Malaria assay and 97.8 % and 98.3 % for the Alethia Malaria assay, respectively. When comparing both molecular assays, high congruency was seen (96.3 %; 158/164). We observed a negative correlation between the EasyNAT reported time-to-positivity and parasitemia, where higher parasitemia resulted in shorter time-to-positivity.The EasyNAT Malaria assay and Alethia Malaria assay show high sensitivity and specificity for malaria screening in the Dutch non-endemic setting. The EasyNAT Malaria assay has the added benefit that it is compatible with laboratory information systems and requires fewer sample handling steps compared with the Alethia Malaria assay. Moreover, time-to-positivity values indicative of low parasitemia may aid laboratories to potentially shorten the diagnostic process for patients with mild symptoms as these patients may be evaluated by the consultant clinical microbiologist without the need for urgent microscopy outside regular office hours.